The effect of 8 weeks of swimming training, cell therapy and vitamin E consumption on testosterone levels and genes involved in the autophagy pathway of infertile male rats - Behnam Esmaeeli; Parvin Farzanegi; Seyed Abdollah Hashemvarzi; Babisan Askari (Mashhad University of Medical Sciences, 2024)
Introduction: Infertility is actually a lack of fertility in couples that has not conceived despite a year or more of trying to reproduce. The present study was performed with aim to investigate the effect of 8 weeks of swimming training, cell therapy and vitamin E consumption on testosterone and Lc31 and P62 genes in the testicular tissue of azoospermia model rats. Methods: In this experimental study, forty 6- to 8-week-old rats were randomly selected, and then the azoospermia model was induced with the busulfan at a dose of 40 mg. After one month, the rats were divided into 8 groups: 1) control, 2) patient, 3) sham, 4) patient + exercise, 5) patient + supplement, 6) patient + cell, 7) patient + supplement + exercise, and 8) patient + cell + exercise. Stem cells were transplanted in the vas deferens at the rate of one million cells for each mouse, they received an oral solution of vitamin E at the rate of 100 mg/kg by gavage, also the training groups performed swimming training continuously with a constant intensity of 60% of the maximum heart rate for 8 weeks, 30 minutes a day, 5 day of the week. Testosterone levels were measured by ELISA and the expression of P62 and LC31 genes in testicular tissue was measured by Real Time PCR technique. Data were analyzed using SPSS statistical software (version 26). P<0.05 was considered statistically significant. Results: Induction of azoospermia significantly decreased testosterone levels and the expression of Lc31 and P62 genes in testicular tissue compared to the control group (P≤0.05), but showed a significant increase in the supplement, cell, exercise, exercise+supplement and exercise+cell groups compared to the patient and sham groups (P≤0.05). Conclusion: In the present study, the synergism of swimming exercise with vitamin E and mesenchymal stem cells derived from bone marrow in improving the autophagy flux in experimental rats with azoospermia was observed, which may be effective in increasing testosterone or even fertility.